Happiness in Cohabitation Relationships: A Phenomenological Study on Catholic Women Who Have Experienced Cohabitation - Veny Mulyani (Universitas Negeri Semarang, 2023)
Cohabitation in Indonesia is considered a violation of eastern morals and religious morals. Cohabitation is considered inappropriate, immoral and living in sin. This study aims to describe (1) the role of religion in happiness in committing cohabitation: (2) happiness in committing cohabitation relationships. This research is qualitative research, using a descriptive phenomenological approach. The method used purposive sampling by selecting 3 Catholic women who had undergone cohabitation, at least 2 year of cohabitation relationship. All the interview were recorded, poured into verbatim and analyzed. There are 4 main themes (couple's attitude, level of happiness, guilt towards God and the desire to get back together). The results of this study are (1) cohabiter women who are still actively participating in religious activities find it difficult to feel fully happy because they are squeezed by the moral burden as religious people who must obey the religious regulations they believe in. (2) Cohabiter women find it difficult to feel fully happy, one of the reason is because of the bad attitude of the partner, and the pressure of social norms that prevailing in society. (3) the desire to get back together after experiencing separation, that happen to women who tend to be happy living with their cohabiting partners and women who have children from their cohabiting partners. Another interesting finding, women who undergo cohabitation relationships also have the potential to be treated badly by their cohabitation partners. The future of the child is also greatly disadvantaged because it bears the stamp of the environment because it was born out of wedlock.